BIMBINGAN DAN PENYULUHAN TENTANG PENTINGNYA MEMBANGUN LOYALITAS PELANGGAN PADA KELOMPOK USAHA JAMAAH MASJID AL IKHLAS RT.07, RW.17, SUDIMORO,MOJOLANGU KEC.LOWOKWARU KOTA MALANG - Joko Samboro; M Maskan; Heru Utomo; Abdullah Helmy; Yosi Afandi; Musthofa Hadi (P3M Politeknik Negeri Malang, 2024)
The purpose of this PKM is to find the problems faced by the congregation of the AL Ikhlas Mosque RT.076 RW.17 Sudimoro, Mojolangu Village, Lowokwaru District, Malang City and at the same time provide the right solution to achieve increased knowledge and skills in the field of marketing management, especially building customer loyalty. The methods used are: observation, to observe activities carried out both in the economic and socio-religious fields, then interviews, explored to find problems and solutions that will be offered and simulations, to find the most appropriate alternatives to market goods more effectively. Description of the technology to be applied. 1. In the form of lectures: Study Group participants are gathered in a certain room and given a lecture on devotion material in the form of: Customer Loyalty. 2. Guidance and Training: In the form of practical guidance and training and discussion of experiences and obstacles in the field. 3. Simulation practice: In the form of a demonstration of how entrepreneurs offer goods, and how to attract potential consumers, until loyal customers are formed Keywords: guidance and counseling, customer loyalty.